2019
DOI: 10.14309/crj.0000000000000295
|View full text |Cite
|
Sign up to set email alerts
|

Acute Esophageal Necrosis Associated With Acute Pancreatitis

Abstract: Acute esophageal necrosis or “black esophagus” is a rare clinical entity characterized by necrosis of the esophageal mucosa resulting from low-flow hemodynamic states. The disease commonly presents with upper gastrointestinal hemorrhage, and the diagnosis is based on the presence of circumferential black appearance of the distal esophagus with variable proximal involvement and sparing of mucosa distal to the esophagogastric junction. The disease is associated with a high mortality rate, and treatment is suppor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Although there are no clinical guidelines in AEN management, it seems reasonable to perform a repeat endoscopy 1 month after initial presentation [9,69]. Delayed complications could appear a few weeks later [70]. The patient in the presented Case Report is a prime example of how that specific agents, such as baking soda, should not be utilised for any purpose other than the use indicated because, used together with the presence of other underlying conditions could be life-threatening.…”
Section: Discussionmentioning
confidence: 97%
“…Although there are no clinical guidelines in AEN management, it seems reasonable to perform a repeat endoscopy 1 month after initial presentation [9,69]. Delayed complications could appear a few weeks later [70]. The patient in the presented Case Report is a prime example of how that specific agents, such as baking soda, should not be utilised for any purpose other than the use indicated because, used together with the presence of other underlying conditions could be life-threatening.…”
Section: Discussionmentioning
confidence: 97%
“…Although the exact pathophysiology of the development of AEN is still unclear, there is consensus that it is caused by a combination of esophageal mucosal injury due to gastric acid and ischemic injury due to vascular compromise [ 9 ]. The vascular supply of the esophagus is unique in that the distal esophagus is relatively sparingly vascularized compared to the proximal and middle portions.…”
Section: Discussionmentioning
confidence: 99%
“…2 Multiple studies and reviews agree that the initial management for AEN is supportive care, resuscitation, and proton pump inhibitors to protect the esophageal mucosa from injury from acid reflux. 2,5,11 In a systematic review that included studies from 1990 to 2018, it was found that most cases of AEN were treated conservatively. Interestingly, the rate of surgical and/or endoscopic intervention (stenting or dilations to treat complications secondary to AEN) was found to be 9.7% before 2006, which increased to 30% afterward.…”
Section: Discussionmentioning
confidence: 99%